MANAGEMENT OF AKHLAQUL KARIMAH DEVELOPMENT AMONG STUDENTS AL-WASHLIYAH 8 MEDAN JUNIOR HIGH SCHOOL - Lingghom Miranda Hanum Pakpahan; Muhammad Fachran Haikal (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2026)
Character education is a vital component in shaping the moral foundation of the younger generation. Accordingly, this study aims to analyze in depth the application of management functions in fostering good character among students at Al-Washliyah 8 Junior High School in Medan. This study employs a comprehensive qualitative approach with a specific focus on narrative research to capture the school community's authentic experiences. Data collection was conducted through in-depth interviews with the school principal, guidance and counseling teachers, and students, supplemented by direct observations and documentation. Data analysis was meticulously performed through data reduction, display, and conclusion drawing, with validity testing firmly established through source and method triangulation. The research findings reveal that character development is systematically executed through the core management functions of planning, organizing, implementing, and supervising. This mentoring program is operationalized through continuous daily religious activities, targeted monthly events, and comprehensive annual programs such as short-term Islamic boarding schools. Furthermore, these initiatives are heavily supported by positive role models from educators and ongoing, constructive supervision. Ultimately, these findings strongly confirm that a structured management approach is indispensable for consistently shaping students’ religious culture, moral integrity, and overall character development.